PENGARUH PENGEMBANGAN KARIER TERHADAP RETENSI APARATUR SIPIL NEGARA (ASN) PADA SEKRETARIAT DAERAH KABUPATEN KERINCI: Ade Nurma Jaya Putra S.Sos., M.A.P - ade nurma jaya (LPPM STIA Nusantara Sakti, 2018)
This study aims to determine the effect of career development on the Retention of the State Civil Apparatus (ASN) in the Kerinci Regency Regional Secretariat, while the population and sample in this study were 68 employees. The analytical tool used in this study is a simple linear regression by conducting a regression test, the results of this study indicate that Career Development has a significant influence on the Retention of State Civil Apparatus. This is evidenced by the results of t-test where tcount> ttable (17,992> 1,677), while the amount of Career Development that is proven by Rsquare is 0.831 or (83.1%), while the remaining 16.9 %% is influenced by other variables